2012
DOI: 10.1111/j.1365-313x.2012.04998.x
|View full text |Cite
|
Sign up to set email alerts
|

nMAT1, a nuclear‐encoded maturase involved in the trans‐splicing of nad1 intron 1, is essential for mitochondrial complex I assembly and function

Abstract: SUMMARYMitochondrial genomes (mtDNAs) in angiosperms contain numerous group II-type introns that reside mainly within protein-coding genes that are required for organellar genome expression and respiration. While splicing of group II introns in non-plant systems is facilitated by proteins encoded within the introns themselves (maturases), the mitochondrial introns in plants have diverged and have lost the vast majority of their intronencoded ORFs. Only a single maturase gene (matR) is retained in plant mtDNAs,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
209
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 121 publications
(226 citation statements)
references
References 92 publications
17
209
0
Order By: Relevance
“…This phenomenon has been reported for other mutants, such as otp43 (Falcon de Longevialle et al, 2007), bir6 (Koprivova et al, 2010), mtsf1 (Haïli et al, 2013), nMat1 (Keren et al, 2012), nMat2 (Keren et al, 2009), nMat4 (Cohen et al, 2014), mcsf1 (Zmudjak et al, 2013), and indh (Wydro et al, 2013), as well as the Nicotiana sylvestris mutant cms2 (Gutierres et al, 1997) and the maize (Zea mays) nonchromosomal stripe1 (Karpova and Newton, 1999). The molecular defect in tang2 is much stronger than that of otp439, and this is reflected by the quantity of the assembled complex I in the mutants, which is very likely the reason behind the discrepancy between their phenotypes.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…This phenomenon has been reported for other mutants, such as otp43 (Falcon de Longevialle et al, 2007), bir6 (Koprivova et al, 2010), mtsf1 (Haïli et al, 2013), nMat1 (Keren et al, 2012), nMat2 (Keren et al, 2009), nMat4 (Cohen et al, 2014), mcsf1 (Zmudjak et al, 2013), and indh (Wydro et al, 2013), as well as the Nicotiana sylvestris mutant cms2 (Gutierres et al, 1997) and the maize (Zea mays) nonchromosomal stripe1 (Karpova and Newton, 1999). The molecular defect in tang2 is much stronger than that of otp439, and this is reflected by the quantity of the assembled complex I in the mutants, which is very likely the reason behind the discrepancy between their phenotypes.…”
Section: Discussionsupporting
confidence: 76%
“…and M. polymorpha also contain several group I introns, the vast majority of the introns in flowering plants (with the exception of the cox1 intron in some species) belong to group II, with 23 in Arabidopsis and rice (Oryza sativa; Bonen, 2008). These introns seem to have lost their self-splicing ability, thus necessitating the help of maturases such as the nuclearly encoded nMAT1, nMAT2, nMAT3, and nMAT4 and possibly the mitochondrial MatR, whose function is still elusive (Keren et al, 2009(Keren et al, , 2012Brown et al, 2014;Cohen et al, 2014). Plant mitochondrial DNA is renowned for its high recombination rates and its ability to integrate foreign DNA sequences, explaining the difficulty of retracing the evolutionary story of group II introns (Bonen, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it was proposed that the gCA subcomplex may play a role in the light-dependent life style of plants (Brauna and Zabaleta, 2007). Several Arabidopsis mutants have been reported that affect proteins of complex I; these mutants showed growth retardation, abnormal leaf morphology, and poor germination (de Longevialle et al, 2007;Keren et al, 2012). A tobacco (Nicotiana tabacum) complex I-specific mutant, CMSII, exhibits decreased photosynthesis at atmospheric Figure 1.…”
mentioning
confidence: 99%
“…To date, there has been little information regarding their changes to explain regulation under different environments because PPR genes are expressed at low levels 47 . Furthermore, group II intron splicing factors besides PPR proteins have been found: MRS2, a homologue of the yeast splicing factor 68,69 , maturases, Marchantia or yeast group II intronic ORF homologs in higher plants 31,32,53,55 , PMH2, a DEAD-box protein 33 , and so on. Information on these genes will help develop environmental tolerances of crops.…”
Section: Perspective Of a Plant Organelle Biological Study Concerninmentioning
confidence: 99%